Mapping Mathematics Unit Allocation in Civil Engineering Programs Across Philippine SUCs: A Basis for Curriculum Enhancement - Vasco Vic G. Valdez; Janvir Moses S. Escalona; Ayesha Amie G. De Leon; Arianne Jean A. David; Roddy Pete D. Mercado (Research Synergy Foundation, 2026)
This study examined mathematics unit allocations in Civil Engineering programs across selected State Universities and Colleges (SUCs) in the Philippines and proposed a data-informed framework for curriculum planning. Using a quantitative document analysis approach, curricular data from 19 SUCs were analyzed using descriptive statistics to determine the total number of mathematics units, the distribution of units across major mathematics courses, and the inclusion of bridging or preparatory mathematics subjects. The Bounded Variability Unit Allocation Model (BVUAM) was applied to generate suggested unit allocations based on observed institutional patterns. Findings revealed considerable variation in the total number of mathematics units across SUCs, particularly in foundational mathematics courses such as Differential and Integral Calculus. Bridging or preparatory mathematics courses also varied widely, with some institutions allocating substantial instructional units while others offered none. In contrast, higher-level and applied mathematics courses remained largely uniform across institutions. The BVUAM-generated recommendations suggested relatively higher allocations for foundational and bridging mathematics while maintaining standard allocations for advanced mathematics courses. The model serves as a descriptive and data-informed framework for examining curriculum allocation patterns and may support curriculum review and planning in Civil Engineering programs.